SPIRITUALITY AND CONTINGENCY IN NARRATIVE BIOGRAPHICAL INTERVIEWS WITH PRIMARY SCHOOL LEADERS OF CATHOLIC SCHOOLS IN THE NETHERLANDS - J. Copier; C.A.M. Hermans; T. Van der Zee (Acta Theologica)
There is a growing interest in personal biographies of school leaders as a source of their leadership qualities. However, it is unclear what aspects of the biography informs these qualities as a school leader. This article proposes to focus on experiences of contingency in biographies of school leaders. Previous research has conceptualised various modes of handling contingency experiences: denial, acceptance and receiving. The authors suggest a new definition of the mode of contingency receiving that overcomes the constructivist bias and encompasses both religious and non-religious interpretations. Based on a qualitative analysis of 35 narrative biographical interviews with school leaders, the authors show that all three modes of handling experiences of contingency are present in biographies of school leaders. The redefined category of contingency receiving can be understood as a spiritual experience that includes experiences of religious and non-religious people reporting transformations in their self-understanding, understanding of the world, and what is of ultimate meaning in life.